Validation of Mental Health Nurses’ Knowledge Questionnaires toward the Sexual Behavior Problems of Mental Disorder Patients through Cultural Adaptation - Suzanna; Intansari Nurjannah; Sri Hartini (The Indonesian Institute of Science and Technology Research, 2022)
One of measurements on nurses’ basic skills regarding patient’s sexual behavior problem is through nurse’s knowledge domain using a structured-questionnaire with structural equation modeling, hypothesis that has been developed in previous studies in Chinese version. Meanwhile, the Indonesia version has not yet beeb developed, especially in the scope mental health services. Objective: Validate a mental health nurse’s knowledge questionnaire on sexual behavior problems in mental patiens. This type research is quantitative using bivariate analysis namely validity and reliability tests. Result showed validity test on 60 respondents of mental health nurses from 31 questions about nurses’s knowledge showed that there were 21 valid items with r count or corrected item values were greater than r table. Meanwhile, in valid items were not used. The result of the reliability test Cronbach’s Alpa value was 0.66 > 0.60, so nurses’ knowledge questionnaire can be said to be reliable. The conclusion explains that 21 items of nurses' knowledge questions were declared valid and reliable and could be used as a standard for measuring nurses' knowledge in patients' sexual problems.